W wężowisku intertekstualnym. Poetica viperina Adama Mickiewicza - Kirschbaum, Heinrich (Slavia Occidentalis, 2014)
The article, theoretically and methodologically situated between postcolonial and intertextuality studies, explores the functioning of serpent imagery in Adam Mickiewicz’s anti-imperial writing. As a metaphor and metonymy, the serpent develops a broad and dynamic range of significations, from an Aesopic figure of Polisch homelessness, treason or rebellion, to a symbol of Russian discursive violence. Snake-as-trope provides Mickiewicz with complex autotextual and intertextual areas of tension and conflict zones where the ethical and aesthetic paradoxes of the political, cultural and literary Wallenrodism are negotiated.